Metabolomic Profile of ARDS by Nuclear Magnetic Resonance Spectroscopy in Patients With H1N1 Influenza Virus Pneumonia. Issue 5 (November 2018) - Izquierdo-Garcia, Jose L.; Nin, Nicolas; Jimenez-Clemente, Jorge; Horcajada, Juan P.; Arenas-Miras, Maria del Mar; Gea, Joaquim; Esteban, Andres; Ruiz-Cabello, Jesus; Lorente, Jose A.
ABSTRACT: Purpose: The integrated analysis of changes in the metabolic profile could be critical for the discovery of biomarkers of lung injury, and also for generating new pathophysiological hypotheses and designing novel therapeutic targets for the acute respiratory distress syndrome (ARDS). This study aimed at developing a nuclear magnetic resonance (NMR)-based approach for the identification of the metabolomic profile of ARDS in patients with H1N1 influenza virus pneumonia. Methods: Serum samples from 30 patients (derivation set) diagnosed of H1N1 influenza virus pneumonia were analyzed by unsupervised principal component analysis to identify metabolic differences between patients with and without ARDS by NMR spectroscopy. A predictive model of partial least squares discriminant analysis (PLS-DA) was developed for the identification of ARDS. PLS-DA was trained with the derivation set and tested in another set of samples from 26 patients also diagnosed of H1N1 influenza virus pneumonia (validation set). Results: Decreased serum glucose, alanine, glutamine, methylhistidine and fatty acids concentrations, and elevated serum phenylalanine and methylguanidine concentrations, discriminated patients with ARDS versus patients without ARDS. PLS-DA model successfully identified the presence of ARDS in the validation set with a success rate of 92% (sensitivity 100% and specificity 91%). The classification functions showed a good correlation with the Sequential Organ Failure Assessment score (R = 0.74, P < 0.0001) and the PaO2 /FiO2 ratio (R = 0.41, P = 0.03). Conclusions: The serum metabolomic profile is sensitive and specific to identify ARDS in patients with H1N1 influenza A pneumonia. Future studies are needed to determine the role of NMR spectroscopy as a biomarker of ARDS.